2018
DOI: 10.1038/s41598-018-27394-1
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of mTOR signaling impact metabolic stress resistance in colorectal carcinomas with BRAF and KRAS mutations

Abstract: Metabolic reprogramming is as a hallmark of cancer, and several studies have reported that BRAF and KRAS tumors may be accompanied by a deregulation of cellular metabolism. We investigated how BRAFV600E and KRASG12V affect cell metabolism, stress resistance and signaling in colorectal carcinoma cells driven by these mutations. KRASG12V expressing cells are characterized by the induction of glycolysis, accumulation of lactic acid and sensitivity to glycolytic inhibition. Notably mathematical modelling confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…Finally, two groups have recently demonstrated that KRAS G12v and BRAF V600E mutations affects metabolic pathways differently in CRC [109, 110]. A proteomics and metabolomics approach by Fritsche-Guenther and colleagues showed that glycolytic flux was upregulated in Caco-2- KRAS G12v cells but decreased in Caco-2- BRAF V600E cells as compared to Caco-2 controls at physiologic glucose levels [110].…”
Section: Rtk-ras Signalingmentioning
confidence: 99%
“…Finally, two groups have recently demonstrated that KRAS G12v and BRAF V600E mutations affects metabolic pathways differently in CRC [109, 110]. A proteomics and metabolomics approach by Fritsche-Guenther and colleagues showed that glycolytic flux was upregulated in Caco-2- KRAS G12v cells but decreased in Caco-2- BRAF V600E cells as compared to Caco-2 controls at physiologic glucose levels [110].…”
Section: Rtk-ras Signalingmentioning
confidence: 99%
“…A previous protocol used in our lab for adherent cells growing under 10% FCS was a modified Bligh-Dyer extraction to separate lipid and polar metabolites [23,24]. The protocol includes the use of 50% MeOH for cell quenching followed by an extraction using a 1:0.4:1, v/v/v MeOH:CHCl 3 :H 2 O ratio.…”
Section: Preliminary Experiments On Phase Separationmentioning
confidence: 99%
“…It is already known that the glycolysis and glutaminolysis of cancer cells can be blocked by using glycolytic inhibitors like 3-Bromopyruvic acid (BrPy) [ 7 , 23 ]. Therefore, we assessed the viability of the OS cell lines treated with BrPy.…”
Section: Resultsmentioning
confidence: 99%
“…The extracts were centrifuged for 10 min at 18,213× g , and aliquots of 25 µL were transferred into glass vials for GC-MS measurements. An identification mixture for reliable compound identification was prepared and derivatized in the same way, and an alkane mixture for a reliable retention index calculation was included [ 7 , 23 , 41 ]. The metabolite analysis was performed on a Pegasus 4D GCxGC TOFMS-System (LECO Corporation, St. Joseph, MN, USA) complemented with an auto-sampler (Gerstel MPS DualHead with CAS4 injector, Mühlheim an der Ruhr, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation